PENGARUH KOMPETENSI DOKTER, PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN MEDICAL CHEK UP RUMAH SAKIT SILOAM LIPPO CIKARANG BEKASI - Nancy Chistiana Muliawan; Darlius (Jurnal Satya Mandiri Manajemen dan Bisnis, 2017)
This reseach aimstoanalyzethe influence of Doctors’ Competetion Nurce’s Service, and Facility in Check up departmen of Siloam Hospital Lippo Cikarang. Through this study the outher can determine the influence that occrs to patiens interest for medicalcheck up. Techniques of data collection with distribution of questionnaire, and sucessfully coolected as many as 200 respondents. Research methods using analysis of Structural Equation Modeling (SEM) Lisrel 8.8 used to help for testing this model. The result shows that Doctors’s Competetion is not affect significanly but Nurce’s Service, and Faclity affect the level of patients interest for medical check up at Siloam Hospital Lippo Cikarang Jawa Barat.